La dimensión dantesca en Borges - Crolla, Adriana (Universidad Nacional del Litoral, 2010)
Borges started his dialogue with the Florence poet’s masterpiece when he was over thirty through a translation by Longfellow and in an English-Italian bilingual book. This reading caused him to develop a linguistic competence solely to approach the work in the original, and was the starting point of a life-long dantesque iter lectoris. Starting from the analysis of a conference in which Borges related the details of that and other important encounters, the present work approaches some aspects of the borgesian exegesis which account for the way in which his reading of the great poem generated a dantesque dimension in his writing and in his world view, and for how the dantesque literary paradigm was reconfigured as a result of borgesian palimpsestic operations.